Comparative Genomics Uncovers the Genetic Diversity and Characters of Veillonella atypica and Provides Insights Into Its Potential Applications - Han, Maozhen; Liu, Gang; Chen, Yajun; Wang, Dong; Zhang, Yan (Frontiers in Microbiology, 2020)
Veillonella atypica is a bacterium with the presence of mammals gut and oral and plays diverse roles in different niches. A recent study demonstrated that Veillonella is highly associated with marathon running and approved that V. atypica gavage improves treadmill run time in mice, which revealed that V. atypica has a high biotechnological potential in improving athlete performance. However, the comprehensive analysis of genetic diversity, function traits, and genome editing method of V. atypica remain elusive. In the present study, we conducted a systemically comparative analysis of genetic datasets of nine V. atypica strains. The pan-genome of V. atypica consisted of 2065 homologous clusters and exhibited an open pan-genome structure. Phylogenetic analysis of V. atypica with two different categories revealed that V. atypica OK5 was the most distant from the other eight V. atypica strains. A total of 43 orthologous genes were identified as CAZyme genes and grouped into 23 CAZyme families. CAZyme components derived from accessory clusters contributed to the differences in the ability of the nine V. atypica strains to utilize carbohydrates. An integrated analysis of the metabolic pathways of V. atypica suggested that V. atypica strains harbored vancomycin resistance and were involved in several biosynthesis pathways of secondary metabolites. The V. atypica strains harbored four main Cas proteins, namely, CAS-Type IIIA, CAS-Type IIA, CAS-Type IIC and CAS-Type IIID. This pilot study provides an in-depth understanding of and a fundamental knowledge about the biology of V. atypica that allow the possibility to increase the biotechnological potential of this bacterium.